Corrigendum to: Cancer Proteomics: New Horizons and Insights into Therapeutic Applications - Subramanian, Perumal; Jayapalan, Jaime Jacqueline; Abdul-Rahman, Puteri S. (Current Proteomics, 2023)
Following the publication of the original article [1], the authors reported that the complete grant number of the funding was omitted. In this correction, the incorrect and correct grant numbers are mentioned. The original publication of this article has been corrected. The funding acknowledgement published previously is as follows: The study was funded by Fundamental Research Grant Scheme (FRGS) by the Ministry of Education, Malaysia, Grant number: FP067-2018A, Geran Penyelidikan Fakulti by the Faculty of Medicine, University of Malaya, Grant number: GPF001C- 2019, and UGC mid-career award, Grant number: F.19-221/2018 (BSR) dt. 28.03.2018. We would like to request a revision to one of the funding numbers (in blue) in the funding acknowledgement below: The correct funding acknowledgement is: The study was funded by Fundamental Research Grant Scheme (FRGS) by the Ministry of Education, Malaysia, Grant number: FRGS/1/2018/STG05/UM/02/5, Geran Penyelidikan Fakulti by the Faculty of Medicine, University of Malaya, Grant number: GPF001C-2019 and UGC mid-career award, Grant number: F.19-221/2018 (BSR) dt. 28.03.2018. The original article can be found online at: https://www.eurekaselect.com/public/article/109117.